2011
DOI: 10.1152/ajpregu.00169.2010
|View full text |Cite
|
Sign up to set email alerts
|

UPR induces transient burst of apoptosis in islets of early lactating rats through reduced AKT phosphorylation via ATF4/CHOP stimulation of TRB3 expression

Abstract: Endocrine pancreas from pregnant rats undergoes several adaptations that comprise increase in β-cell number, mass and insulin secretion, and reduction of apoptosis. Lactogens are the main hormones that account for these changes. Maternal pancreas, however, returns to a nonpregnant state just after the delivery. The precise mechanism by which this reversal occurs is not settled but, in spite of high lactogen levels, a transient increase in apoptosis was already reported as early as the 3rd day of lactation (L3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 48 publications
6
71
0
2
Order By: Relevance
“…As a key mediator of ER stress-induced apoptosis, CHOP mediates cell death primarily through two mechanisms: alters the transcription of genes involved in apoptosis and oxidative stress [38,39] and relieves the inhibition of protein translation imposed by PERK signaling (via induction of GADD34 expression) through a feedback loop [40]. In this study, it was found that rTcdB induced the up-regulation of CHOP at transcriptional level ( Fig.…”
Section: Discussionmentioning
confidence: 57%
“…As a key mediator of ER stress-induced apoptosis, CHOP mediates cell death primarily through two mechanisms: alters the transcription of genes involved in apoptosis and oxidative stress [38,39] and relieves the inhibition of protein translation imposed by PERK signaling (via induction of GADD34 expression) through a feedback loop [40]. In this study, it was found that rTcdB induced the up-regulation of CHOP at transcriptional level ( Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, the apoptosis and expression of CHOP were reduced in atherosclerotic lesions of D4F-treated apoE Ϫ / Ϫ mice. The translocation of ATF6 to the nucleus and phosphorylation of PERK play critical roles in the ER stress-CHOP pathway ( 8,31,32 ). Recently, we showed that ATF6 and PERK upregulate CHOP expression and subsequently mediate ox-LDLinduced apoptosis in macrophages ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PERK in response to ER stress leads to eukaryotic initiation factor 2 alpha (eIF2α) phosphorylation and transient protein synthesis inhibition. This block in translation leads to the synthesis of activating transcription factor 4 (ATF4), which binds to the C/EBP-ATF composite site and transactivates the CHOP promoter 25,33) . We here showed that the phosphorylation of PERK was induced in the presence of ox-LDL, and PERK-specific siRNA also inhibited the ox-LDL-induced upregRecently, CHOP-mediated apoptosis in macrophages has been demonstrated to contribute to the instability of atherosclerotic plaques, and CHOP deficiency has been found to protect macrophages from ER stress-induced apoptosis in vitro and in advanced atherosclerotic lesions of mice 17,24,29,30) .…”
Section: Atf6 Sirna Attenuates Ox-ldl-induced Apoptosis Of Raw2647 Cmentioning
confidence: 99%